Firm-Specific Risk-Neutral Distributions with Options and CDS - Aramonte, Sirio; Jahan-Parvar, Mohammad R.; Rosen, Samuel; Schindler, John W. (Management Science, 2022)
We propose a method to extract the risk-neutral distribution of firm-specific stock returns using both options and credit default swaps (CDS). Options and CDS provide information about the central part and the left tail of the distribution, respectively. Taken together, but not in isolation, options and CDS span the intermediate part of the distribution, which is driven by exposure to the risk of large, but not extreme, returns. Through a series of asset-pricing tests, we show that this intermediate-return risk carries a premium, particularly at times of heightened market stress. This paper was accepted by David Simchi-Levi, finance.